Soils of Malaysia - Ashraf, Muhammad Aqeel (Boca Raton : Taylor & Francis, 2017)
"There are approximately 500 different types of soils in Malaysia, most is residual soil and coastal alluvial soil. It covers topics including climate; flora and fauna; geology and hydrology; land use changes for agriculture; soil fertility; human-induced soil degradation; and soil contamination sources. "--Provided by publisher.
chapter 1 Climate, Ecosystem, Flora, and Fauna -- chapter 2 Geology and Hydrology -- chapter 3 Landuse for Agriculture in Malaysia -- chapter 4 Major Soil Type, Soil Classification, and Soil Maps -- chapter 5 Soil Properties (Physical, Chemical, Biological, Mechanical) -- chapter 6 Agricultural Soil Contamination -- chapter 7 Soil Fertility and Management of Malaysian Soils -- chapter 8 Future Soil Issues.
Keywords: Soils -- Malaysia